PERANCANGAN ARSITEKTUR SISTEM INFORMASI MANAJEMEN DAN AKADEMIK SDN BABADAN 01 DENGAN ZACHMAN FRAMEWORK - Muhammad Zahid Abid; Rahmawan Ilham Pratama; Agatha Putra Yudha Purnomo; Hani Atun Mumtahana (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2023)
Industry  4.0 develops in Indonesia and the Covid-19 Pandemic, all business process activities are required to be able to adapt by digizing service. For SDN Babadan 01 itself, the business process is still using the old method which requires all processes to be carried out directly face to face such as registration of new students and is not yet effective. Therefore the design of Management and Academic Information System  is needed to support the business processes that are carried out. With the creation of a Management Information System and Academic Information System, it is hoped that it can help facilitate all academic  and non-academic matters at SDN Babadan 01. For data collection , interviews and literature studies were used. This study uses the Zachman Framework which consist of 6 columns and 6 rows. Based on the research that has been done, the design of SIAKAD and SIM at SDN Babadan 01 has resulted. This design can be used as a reference for application developers.